Temperature-Dependent Dielectric Properties of Foods during Freezing and Thawing - Isaksson, Sven; Sadot, Mathieu E.; Da Silva, Ana N.; Curet, Sébastien; Rouaud, Olivier; LeBail, Alain; Havet, Michel; Xanthakis, Epameinondas (My University, 2017)
Dielectric properties of a variety of foodstuffs were measured during freezing and thawing conditions, and are presented here as functions of temperature. Measurements were done with the Agilent 85070 high temperature dielectric probe. The differences in characteristics of the graphs resulting from cooling and thawing are discussed. A specific model accommodating the amount of frozen water in the food sample as a function of temperature is used and compared to experimental results. The mass fraction of each component is coupled to the dielectric properties of each fraction to evaluate the effective dielectric properties based on a two phases Maxwell-Wagner model considering ice as a dispersed fraction and food as a continuous fraction. The unknown dielectric properties of dry matter and an adjusting coefficient are used to optimize the fitting between experimental data and calculated data.
Keywords: Microwave; Dielectric properties; Food; Freezing; Thawing